Gratitude (shukr) group intervention for promoting college students’ well-being: A quasi-experimental study - Melati Sumari; Dini Farhana Baharudin; Amira Najiha Yahya; Yusni Mohamad Yusop (Elsevier BV, 2026)
Indexed by SCOPUS